PENGARUH KEMASAN, MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN KACANG GARUDA ( Studi kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang ) - M. Fasih Zunaidy; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe purpose of this study was to describe the packaging, brands, prices, and purchasing decisions and to determine the effect of packaging, brands, and prices on purchasing decisions simultaneously and partially. This research method uses quantitative methods. This type of research is explanatory research.The sample of this research is Malang Islamic Economics and Business students using saturated sampling, which is as many as 83 respondents. Data collection method uses a questionnaire. The analytical method used in this study is multiple regression analysis with SPSS 14.0 four windows.The results this study indicate that: (1) There is a positive and significant effect of packaging on students of the Faculty of Economics and Business Faculty of Malang Islamic University. (2) There is a positive and significant influence of brands on students of the Faculty of Economics and Business, Malang Islamic University. (3) There is a positive and significant price effect on students of the Faculty of Economics and Business at the Islamic University of Malang.Keywords: Packaging, Brand, Price, and Purchase Decision